MEMBANGUN KARAKTER ANTI KORUPSI MELALUI PENDIDIKAN KEWARGANEGARAAN DI SEKOLAH TINGGI - Ninawati, Mimin; Adawiyah, Arifatul; Nuryolanda, Ike; Maura Febriyanti Zulkarnain; Siti Afifah Fadhilah; Siti Nur Aida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Civic Education is a strategic tool that can be used to build a moral national character and stop corruption in Indonesia. The purpose of this study is to see how cognitive learning (Civics Education) contributes to the formation of young people who have critical understanding, responsibility, and democratic attitudes in facing social challenges, including the threat of corruption. The moral condition of the younger generation is very important to pay attention to, especially because corruption endangers the government and the survival of the nation. The method used in this research is to analyze relevant literature, including books and journals that discuss the role of Civics in character building and efforts to eradicate corruption.The research shows that Civics can instill anti-corruption values such as honesty, responsibility, and courage through moral and cultural education methods. As part of the mental revolution, these values shape the character of the younger generation. In addition, incorporating anti-corruption values into the formal school curriculum can be a big step towards establishing a culture of integrity in society. This study shows that strengthening Civics Education is essential to make people understand their rights and obligations as citizens and commit to building a clean and transparent government.